Murine granulated metrial gland cells are susceptible to Chlamydia psittaci infection in vivo. - Sánchez, J (1996)
Granulated metrial gland (GMG) cells are the most numerous lymphoid cells in the uteroplacental unit in rodent pregnancy. In an experimental murine model of abortion-causing infection, we have studied the responses of GMG cells to Chlamydia psittaci. Chlamydial inclusions have been found within GMG cells, both in apparently healthy cells and in cells with degenerative changes. Establishing the existence of GMG cells infected by C. psittaci opens a new and interesting chapter in the study of these cells.